The archaeology of Athens - Camp, John McK. (Yale University Press, 2001)
The monuments of ancient Athens and Attica give eloquent testimony to the enduring legacy of Greek civilization. In this book, a leading authority on the archaeology of this area presents a survey of the monuments, first chronologically and then site by site, creating the definitive work on the subject. John M. Camp begins with a comprehensive narrative history of the monuments from the earliest times to the sixth century A.D. Drawing on literary and epigraphic evidence, including Plutarch's biographies, Pausanias's guidebook, and thousands of inscriptions, he discusses who built a given structure, when, and why. Camp presents dozens of passages in translation, allowing the reader easy access to the variety and richness of the ancient sources. In effect, this main part of the book provides an engrossing history of ancient Athens as recorded in its archaeological remains. The second section of the book offers in-depth discussions of individual sites in their physical context, including accounts of excavations in the modern era. Written in a clear and engaging style and lavishly illustrated, Camp's archaeological tour of Athens is certain to appeal not only to scholars and students but also to visitors to the area